Pengembangan Kreativitas Anak melalui Pelatihan Pembuatan Bros Kain Perca di Dusun Tanah Embet Barat - Ni Ketut Ayu Citra Trisnasari; I Wayan Rudiarta; Ida Bagus Alit Arta Wiguna; I Komang Widya Purnama Yasa (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The development of children's creativity in rural areas faces challenges, especially the limited facilities and the lack of structured productive activities. West Tanah Embet Hamlet has local potential in the form of patchwork waste from household businesses, but it has not been utilized optimally. Training on making patchwork brooches is carried out to increase children's skills, creativity, confidence, and awareness of the use of waste into valuable products as a medium of creative education and introduction to entrepreneurship from an early age. The methods used include initial observation to identify needs and potentials (with SWOT analysis), communication with related parties, direct training, practice, and evaluation of the results. This activity was carried out for 6 meetings involving 23 children aged 7-12 years. The results showed that 45% of participants were able to complete at least 2 brooches with floral and butterfly designs, 70% of participants were able to cut fabrics according to patterns, come up with spontaneous innovations in color combinations and embellishments, and show improved aesthetic and cooperation skills. This program not only provides technical skills in sewing, but also succeeds in adding ideas, forming a creative and collaborative character that can produce a variety of unique products, and has the potential to be developed as a creative economy model based on local resources.